Use of technological tools for gerontological assessment during the COVID-19 pandemic - Solís Canal, Raquel Judith (2022)
Objective: To use technological tools for gerontological assessment during the COVID-19 pandemic. Method: A descriptive, quantitative, cross-sectional study was conducted. Thirty people over 60 years of age with a mobile device or computer, and internet connection were included.  Results: Strengths and limitations of technological tools were identified, as well as the most used means of communication by the elderly during the COVID-19 pandemic, and results were obtained on the geronto-geriatric assessment scales that evaluated affective state, cognitive state, family functionality and mistreatment. Conclusions: Technological tools are useful for social research, but present limitations for the search of qualitative and quantitative data in elderly people, however, this modality should be considered for the timely identification of various alterations in the functional, cognitive, affective, nutritional and environmental status.